2020
DOI: 10.17221/47/2020-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of boar semen

Abstract: Sperm cryopreservation is the best technology for long-term storage of the semen. However, the damage of boar spermatozoa by cryopreservation is more severe than in other animal species and a standardized freezing protocol for efficient cryopreservation has not been established yet. Semen quality and freezability vary greatly between breeds as well as between individual boars and even the season. Boar spermatozoa are sensitive to low temperatures; they sustain damage and a high rate of mortality and freezing/t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 71 publications
(97 reference statements)
1
26
0
1
Order By: Relevance
“…Inter-sire effect in the present study was observed in healthy mature animals of the same breed, in the same breeding conditions, with the semen collected and processed in the same manner. These results are supported by the previously reported inter-sire effect in livestock (Dolezalova et al 2016;Jovicic et al 2020) and in rams (D'Alessandro and Martemucci 2003;Ramon et al 2013). To this matter, the general recommendation can be to select the Wallachian rams with the best sperm viability after thawing for the preparation of insemination doses as one of the criteria in the cryopreservation program.…”
Section: Inter-sire and Daily Variation Impacted The Viability Of Thawed Wallachian Ram Spermsupporting
confidence: 77%
See 2 more Smart Citations
“…Inter-sire effect in the present study was observed in healthy mature animals of the same breed, in the same breeding conditions, with the semen collected and processed in the same manner. These results are supported by the previously reported inter-sire effect in livestock (Dolezalova et al 2016;Jovicic et al 2020) and in rams (D'Alessandro and Martemucci 2003;Ramon et al 2013). To this matter, the general recommendation can be to select the Wallachian rams with the best sperm viability after thawing for the preparation of insemination doses as one of the criteria in the cryopreservation program.…”
Section: Inter-sire and Daily Variation Impacted The Viability Of Thawed Wallachian Ram Spermsupporting
confidence: 77%
“…Such equilibration procedure was reported as a usual procedure for ram sperm (Lv et al 2019). Nevertheless, there exists a recommendation to add glycerol immediately just before the sperm freezing (Jovicic et al 2020). This recommendation might be well-reasoned because of the known glycerol toxicity, as Domingo et al (2019) reviewed.…”
Section: Cryopreservation Decreases the Viability Of Wallachian Ram Spermmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with studies of red deer (Ramon et al 2012) andboars (Flores et al 2009), in which the males with poor freezability were characterised by a high percentage of the sperm subpopulation with low kinematic parameters. Cryopreservation in boars is a long-term challenge (Jovicic et al 2020), similarly like in stallions, because the sperm are highly sensitive to cold shock and both species have a high proportion of seminal plasma in the semen; studies conducted on boar sperm may therefore provide a comparison for our results in stallions. The mitochondrial activity was also lowest in poor freezer boars, and in addition, Hernandez et al (2006) identified less homogeneous chromatin in PF boars.…”
Section: Incubation Time T30mentioning
confidence: 99%
“…Pig arti cial insemination (AI) has been widely used in recent years, and the sperm storage at 17℃ has important signi cance in commercial production [8,22]. Pig sperm is extremely sensitive to temperature changes especially low temperature [15,32]. The cold shock caused by low temperature has a serious impact on sperm quality and the fertilization potential of sperm [13,25,31].…”
Section: Introductionmentioning
confidence: 99%